Hubungan kepadatan megabentos dan padatan tersuspensi terhadap tutupan terumbu karang pada Kawasan Konservasi Pesisir dan Pulau-Pulau Kecil (KKP3K) Tapanuli Tengah, Sumatera Utara - Bima Wahyu Nugroho; Rifardi Rifardi; Thamrin Thamrin (Pelantar Press, 2022)
This research was conducted in March 2022 in the Marine Conservation Area, Tapanuli Tengah Sumatera Utara. This study aims to determine the relationship between coral cover, total suspended solid and the density of megabenthos found in the Marine Conservation Area, Tapanuli Tengah Sumatera Utara. The method used in this study is a survey method and spatial analysis tools method. Coral cover data was collected using the LIT (Line Intercept Transect) method and megabenthos data was collected using the BBT (Benthos Belt Transect) method. The results showed that Marine Conservation Area, Tapanuli Tengah, Sumatera Utara had a good percentage of coral cover. Not all types of megabenthos are present at every station, the highest density of megabenthos is Tridacninae, while the lowest density is Acanthaster planci. Then it was also found that there was an effect of the percentage of coral cover on economic and non-economic megabenthos. Total suspended solid consentration in this area was found with an average of 8.27 mg/l. Based on the regression analysis in this study, showed that there was an effec of total suspended solid on percentage of coral cover.